Combined effect of hydrogen sulphide donor and losartan in experimental diabetic nephropathy in rats. Issue 1 (December 2015) - Kaur, Manpreet; Sachdeva, Shilpi; Bedi, Onkar; Kaur, Tavleen; Kumar, Puneet
Abstract Background Diabetic nephropathy (DN) is one of the complex complications of Diabetes Mellitus (DM). The present study has been designed to examine protective role of hydrogen Sulphide (H2 S) donor against streptozotocin (STZ) -induced behavioral, oxidative abnormalities and its DN like symptoms in rats. Methods For the induction of DN single intraperitoneal administration of STZ (45 mg/kg) was given till third week. Behavioral parameters were measured on 1st, 7th, 21st and 42nd days and biochemical parameters were performed on 42nd day. All the drug treatments [NaHS (10 & 30 μmol/kg i.p), DL-propargylglycine (10 mg/kg i.p), standard drug- Losartan (5 mg/kg p.o)] were given for 3 weeks staring from 21st day after the STZ injection. Results Three weeks treatment with sodium hydrosulphide (NaHS) (10 and 30 μmol/kg i.p, ) significantly attenuated the behavioral and biochemical abnormalities in STZ-treated animals. DL-propargylglycine (10 mg/kg i.p) pretreatment with sub-effective dose of NaHS (30 μmol/kg i.p) significantly reversed the protective effect of NaHS. However, combination of both NaHS (30 μmol/kg i.p) and standard drug losartan (5 mg/kg p.o) potentiated their effects as compared to their effect alone. Conclusion The results of the present study suggest that H2 S treatment showed significant improvement in behavioral and biochemical abnormalities induced by STZ administration. Thus H2 S represents a target of treatment to prevent the progression of complications by DN.